Environmental Pollution in Tintaya - Pinto Herrera, Honorio (2014)
This work is an approach to environmental problems in the mining complex Tintaya (Cusco). It seeks to prove that this problem is structural and long lasting. Content describes and tries to explain the most important facts that show environmental pollution in that place in a period of approximately thirty (30) years, from the 80s of the twentieth century to the present. Limitations of time and financial resources have hindered a more detailed study; also the state and the mining company does not provide access to transparent information in relation to the environmental problem.